Holocene accumulation and ice flow near the West Antarctic Ice Sheet Divide ice core site. Issue 5 (7th May 2016) - Koutnik, Michelle R.; Fudge, T. J.; Conway, Howard; Waddington, Edwin D.; Neumann, Thomas A.; Cuffey, Kurt M.; Buizert, Christo; Taylor, Kendrick C.
Abstract: The West Antarctic Ice Sheet Divide Core (WDC) provided a high‐resolution climate record from near the Ross‐Amundsen Divide in Central West Antarctica. In addition, radar‐detected internal layers in the vicinity of the WDC site have been dated directly from the ice core to provide spatial variations in the age structure of the region. Using these two data sets together, we first infer a high‐resolution Holocene accumulation‐rate history from 9.2 kyr of the ice‐core timescale and then confirm that this climate history is consistent with internal layers upstream of the core site. Even though the WDC was drilled only 24 km from the modern ice divide, advection of ice from upstream must be taken into account. We evaluate histories of accumulation rate by using a flowband model to generate internal layers that we compare to observed layers. Results show that the centennially averaged accumulation rate was over 20% lower than modern at 9.2 kyr before present (B.P.), increased by 40% from 9.2 to 2.3 kyr B.P., and decreased by at least 10% over the past 2 kyr B.P. to the modern values; these Holocene accumulation‐rate changes in Central West Antarctica are larger than changes inferred from East Antarctic ice‐core records. Despite significant changes in accumulation rate, throughout the Holocene the regional accumulation pattern has likely remained similar to today, and the ice‐divide position has likely remained on average within 5 km of its modern position. Continent‐scale ice‐sheet models used for reconstructions of West Antarctic ice volume should incorporate this accumulation history. Key Points: Holocene accumulation‐rate history is inferred from an ice‐core record The inferred accumulation history is validated by radar‐detected internal layers Evaluating the model fit to observed internal layers constrains the ice‐flow history